Detecção de metalo beta lactamase em Pseudomonas aeruginosa isoladas de pacientes hospitalizados - GONÇALVES, Diana Christina Pereira Santos (2009)
P. aeruginosa is frequently isolated in hospitals and the clinical importance has been increased due to gravity of infections. The metallo-beta-lactamase (MBL) production is an emergent mechanism of resistance in P. aeruginosa. The study aimed to determine the antimicrobial susceptibility profile of P. aeruginosa isolated of patients admitted in a hospital in Goiânia, to verify the MBL production by diffusion test and detect MBL genes by PCR technique. A total of 75 samples were evaluated, isolated of various clinical samples, in the period of January/2005 to January/2007. The biochemical identification was performed by automation technique system (API 20E ®) and antimicrobial susceptibility profile by Kirby- Bauer method. The 75 P. aeruginosa presented multi-drug resistance and, the resistance profile was: 90.7% to ceftazidime: 30.7% to aztreonam, 97.3% to ciprofloxacin; 48.0% of resistance to piperacilin/tazobactam, 88.0% to cefepime; amicacin, gentamicin and tobramicina whit resistance profile of 78.7%, 84.0% and 77.4%, respectively. The MBL production by difusion disc method was 46.7% (35/75). The gene blaSPM-1 was detected in 39 (52.0%) and gene blaIMP-1 in three (4.0%) isolates. The high frequency of P. aeruginosa resistant and MBL production alert to necessity of control the dissemination of bacteria multi-drug resistant in hospital, as well as the adoption of preventive actions and explanation of the health workers about rational use of antibiotics.